JOB SATISFACTION IN HIGHER EDUCATION: A CASE STUDY IN SPAIN - Saraiva, Margarida (2018)
In the University System, the satisfaction of teachers is an essential component to increase their professional performance and achieve an adequate level of quality in the services offered to students, thus guaranteeing the proper functioning of the academic center and its results. The main objective of this research is to know the level of job satisfaction of teachers in the Faculty of Business, Finances and Tourism of the University of Extremadura (Cáceres-Spain), and as secondary objectives, to know the level of quality perceived by the teachers of the services offered to the students and to identify the motivations that prompted them to choose the teaching activity for their professional life. To reach the objectives, the methodology used is a descriptive study with a quantitative approach. After a, thorough review of the literature, the collection of the questionnaire was designed and carried out by email to the 74 teachers who formed the center's staff in the academic year 2016-2017, reaching a response rate of 79.72% (59 teachers). The analysis of the data obtained allowed to reach the proposed objectives, obtaining as main result that the teachers respondents indicated to be satisfied with their work. In relation to the quality perceived by the teachers of the services that are provided to the students, these indicate that there is a good quality of the services, being necessary to make investments in the facilities of the Center. The main motivation for the choice of the teaching career is in the first place, the vocation, followed by that teaching fits well with their skills, and thirdly, that it allows them to give a service to society.